Pengembangan Naskah Opini Sistem Reproduksi Pada E-Magazine Berbasis Hots - Dhoti, Shofi Ma'rifaturriya; Suryawati, Evi; Darmadi, Darmadi (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2025)
This study aims to produce a quality reproductive system Opinion Paper on HOTS-based E-Magazine. This Research & Development (R&D) study adapted the ADDIE model to the product development stage. The Opinion Paper was developed in the Biology Education study program, Faculty of Teacher Training and Education, University of Riau until the first trial stage and in SMAN Plus Riau Province in the second trial stage in October 2023-November 2024. The validation was assessed by 4 validators consisting of 2 Biology Education lecturers from University of Riau and 2 Biology teachers from SMAN Plus Riau Province and SMAN 1 Pekanbaru, covering aspects of content, pedagogical, linguistic, and presentation feasibility. The results of the Opinion Manuscript validation obtained very valid criteria (3.79). The results of trial I obtained very good criteria (3.92) and the results of trial II obtained very good criteria (3.96). Overall, the average score of validation, trial I and trial II obtained an average score of 3.89 with very good criteria. The results of this  study indicate that the reproductive system Opinion Paper on HOTS-based E-Magazine that has been developed has the potential to improve HOTS and can be used as an alternative learning resource in Biology learning in grade XI SMA.